2015
DOI: 10.1039/c5cp04666a
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical prediction of silicene as a new candidate for the anode of lithium-ion batteries

Abstract: Using density functional theory calculations, we determine the band structure and DOS of graphene and silicene supercell models. We also study the adsorption mechanism of Li metal atoms and Li-ions onto free-standing silicene (buckled, θ = 101.7°) and compare the results with those of graphene. In contrast to graphene, interactions between Li metal atoms and Li-ions with the silicene surface are quite strong due to its highly reactive buckled hexagonal structure. As a consequence of structural properties the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 52 publications
1
38
0
1
Order By: Relevance
“…The corresponding binding energy is -2.41 eV, which is agreed with other previous works. 18,19,22 The second favorable adsorption site is the valley (V) site on top of the lower silicon atoms with the binding energies of -2.02 eV.…”
Section: Effect Of Strain On LI Adsorptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The corresponding binding energy is -2.41 eV, which is agreed with other previous works. 18,19,22 The second favorable adsorption site is the valley (V) site on top of the lower silicon atoms with the binding energies of -2.02 eV.…”
Section: Effect Of Strain On LI Adsorptionmentioning
confidence: 99%
“…[14][15][16][17] Similar to graphene, silicene provides a large surface area for adsorption and migration of Li. Theoretical studies have shown that the binding energy between Li and single-layer silicene is ~2.2 eV per Li atom while the barriers for Li diffusion are less than 0.4 eV, 18,19 much lower than that of Li diffusion on graphene. 20,21 Moreover, in contrast to crystalline silicon, silicene does not suffer from irreversible structural changes during lithiation and delithiation cycles and the associated change in the effective volume is small.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, silicene is also expected to be a good candidate for LIB electrodes because of its nature of low-dimensional silicon and structural similarity to graphene. In fact, theoretical studies have indicated that the binding energy between Li and silicene is 2.2 eV per Li atom and the barriers for Li diffusion are less than 0.6 eV, [17,18] much…”
mentioning
confidence: 99%
“…Portanto, o siliceno seria, a princípio, umótimo substituto do carbono noânodo. Além disso, a capacidade dô anodo das baterias atuais podem ser, teoricamente, melhorada com a substituição de carbono por outros materiais [13]. Dentre as diversas dificuldades encontradas em se propor novos materiais para oânodo, citam-se a grande expansão em volume, capacidade baixa de transporte de elétrons e diminuição da capacidade com o uso, mostrando deterioração durante os ciclos.…”
Section: Capítulo Introduçãounclassified